A Comparative Literary Analysis of Women’s Power in Public and Private Life in “the Handmaid’s Tale” and “the Awakening” - Noor Saad Abd aljaleel; Hayder Mohammed Abed; Abdulazeez Taha Ahmed (Eximia, 2024)
This paper aims to contrast the novel "The Handmaid’s Tale" by Margaret Atwood to the novel "The Awakening" by Kate Chopin in terms of how women are treated in public and private life. Both novels provide perspectives on women’s roles and power dynamics in various historical circumstances. This paper investigates how literature challenges social norms that affect women’s independence and identity. In this paper, the researcher uses an intersectional feminist framework developed by Crenshaw in order to compare the two narratives using literary analysis and feminist criticism. It looks at the attempts of the main characters to be independent in an oppressive society. The findings indicate that both novels represent women’s universal struggles for autonomy and identity. The themes of resistance, the influence of history and society on women’s roles, and the importance of literature as a means of social critique are highlighting in these two novels. This paper emphasizes that writing such stories can help change societies. Finally, it suggests further studies in different cultural contexts and media and shows how intersectional approaches assist in understanding women’s experiences and resistance.